2017
DOI: 10.1111/vco.12304
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of extracellular cyclicAMP‐dependent protein kinase as a biomarker of cancer in dogs

Abstract: Our data strongly propose that detection of serum ECPKA level is a potential and specific diagnostic tool for cancer in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…The finding of a significantly higher serum ECPKA‐Ab level in dogs with cancer in our present study (Figures and ) is consistent with our previous findings in dogs . Moreover, when the cancers were classified, as shown in Table , the ECPKA‐Ab level was found to be increased regardless of the cell of origin (Figure B) and was significantly higher in the cancer group than in the healthy group; this finding has also been reported in human patients .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding of a significantly higher serum ECPKA‐Ab level in dogs with cancer in our present study (Figures and ) is consistent with our previous findings in dogs . Moreover, when the cancers were classified, as shown in Table , the ECPKA‐Ab level was found to be increased regardless of the cell of origin (Figure B) and was significantly higher in the cancer group than in the healthy group; this finding has also been reported in human patients .…”
Section: Discussionsupporting
confidence: 92%
“…ECPKA has been found to be higher in serum samples from human patients with cancer than in those from individuals without cancer, suggesting its potential as a powerful diagnostic marker of cancer in humans . In a previous study, we demonstrated a significant elevation in ECPKA levels in serum samples from dogs with cancer and suggested that ECPKA could be an important candidate diagnostic biomarker of canine malignancy . However, although ECPKA is a powerful predictor of canine cancer, it is a fragile enzyme in certain situations.…”
Section: Introductionmentioning
confidence: 80%
“…The aim of this study was to demonstrate the increase in AniScan ECPKA antibody levels in dogs bearing malignant tumors compared to non-tumor groups and to evaluate the usefulness of this approach for detecting malignant tumors in dogs. A significantly higher ECPKA antibody level was found in various malignant tumor groups than control groups, as shown in previous studies with regard to canine malignant tumors [13,14]. In human medicine, abundant evidence shows that ECPKA activity or the ECPKA autoantibody level increases in various malignant tumors regardless of the type of tumor or location, including bladder, breast, cervical, colon, esophageal, gastric, liver, lung, ovarian, pancreatic, prostate, renal, renal cell, small bowel, rectal, and adenocystic carcinomas; melanoma; sarcoma and thymoma; liposarcoma; and leiomyosarcoma [8].…”
Section: Discussionsupporting
confidence: 84%
“…Evidence shows that the activity of ECPKA increases in various malignant tumors in human medicine [8][9][10][11], and a report demonstrated that ECPKA activity decreased after surgical removal in human melanoma patients [12]. However, although it is suggested that the ECPKA level also increases in malignant tumors in mammals other than humans, few studies regarding ECPKA are available in the veterinary literature [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Since this methodological approach is currently employed in determining the PKA levels in blood samples, we also included four different sera in our own analysis [ 22 , 30 ]. As expected, four out of four sera exhibited O.D.…”
Section: Resultsmentioning
confidence: 99%